Proactive personality at work: seeing more to do and doing more? - Bergeron, Diane; Kriz, Tiffany; Martinez, Hector A. (My University, 2014)
Purpose: The purpose of this study was to develop and test a model relating proactive personality to job behaviors (task and citizenship behaviors) through the intervening mediator of perceived role breadth. Design/methodology/approach: Survey data were obtained from 530 faculty members in 69 U. S. research universities. Findings Proactive personality was positively related to task behavior and OCB. Perceived role breadth mediated the relationship between proactive personality and OCB, but did not mediate the relationship between proactive personality and task behavior. Despite not viewing their role more broadly, individuals higher in proactive personality engaged more frequently in both task behavior and OCB; and also worked more hours per week. Implications: Having a better understanding of proactive individuals is important in terms of managing them. Because these individuals tend to do more in their jobs and subsequently work more hours, they may be more susceptible to burnout and may require additional help in determining priorities and balancing their work and lives. Originality/value: This is the first study to show that proactive personality is positively related to the frequency with which these individuals engage in task and citizenship behavior. Although role breadth is generally an antecedent of such job behaviors, individuals higher in proactive personality engage more frequently in task behaviors regardless of whether or not they perceive them as part of their role. This is one of the first studies to show that working more hours each week is a potential cost of having a proactive personality.
Keywords: proactive personality; perceived role breadth; organizational citizenship behavior; task behavior; job performance; hours worked